PENGARUH TEKNOLOGI INFORMASI DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA BANK SYARIAH DI INDONESIA PERIODE 2018-2024 - Harun Nur Jamiel; Anandhiya Intan Prabandari (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
The rapid development of Islamic banking in Indonesia demands optimization of performance, including operational efficiency and profitability, to maintain competitiveness. This study examines how information technology and human resource quality influence the efficiency and profitability of Islamic banks in Indonesia during the period 2018-2024. Research data is derived from published financial reports of Islamic banks in Indonesia. Regression analysis is used to examine the relationship between variables, considering bank size and economic growth factors. The results show that information technology significantly contributes to improved operational efficiency and profitability. Technology implementation enables process automation, increased data accuracy, and expanded service reach. Quality human resources, indicated by education and training levels, also have a positive influence. Competent employees are able to optimize technology and provide excellent service to customers. These findings emphasize the importance of continuous investment in information technology and human resource development for Islamic banks. This strategy is crucial to increase operational efficiency and profitability, as well as strengthen competitiveness in the Islamic banking industry.